BEMÖTAS-principen - Aulin, Gustav (2010)
The thesis is about integration in the city and how integration can be improved through physical planning. Segregation can result in changing peoples’ prerequisites in our society. Opportunities in life become dependent on what area of the city you live in or where you grew up. Integration denotes acceptance for all people, while different cultural and ethnic identities are preserved at the same conditions for everyone. Through literature studies, seven different approaches to improve integration through physical planning have been encountered. These are described with theories, examples and discussions. The seven are: Safety, Transitional zones, Attractiveness, Residents’ involvement, Mixed housing, Assembly points, and Connection to the city. The first letter from each one of the seven approaches forms the word STARMAC that also gave this thesis its name. Individually, there is a very limited effect in improving integration with the different approaches. To achieve this, a combination of as many as possible of the seven is required. But integration is never a direct result, even with a combination of the approaches. It should rather be seen as a long process. Hopefully this thesis broadens urban planners’ perspective on their ability to influence people, which can lead to a better and more pleasant society. A society without prejudice and discrimination.